Distinctive microbiota of delayed healing of oral mucositis after radiotherapy of nasopharyngeal carcinoma - Jiang, Rui; Liu, Yafang; Zhang, Han; Chen, Yitang; Liu, Ting; Zeng, Jindi; Nie, Ermin; Chen, Songling; Tan, Jizhou (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Oral mucositis is the most common complication after radiotherapy of nasopharyngeal carcinoma (NPC). Previous studies had revealed that oral microbiota took great alteration soon after and during radiotherapy. Here, we aimed to investigate if the alteration of oral microbiota was related to delayed healing of oral mucositis after six month of radiotherapy. Methods: We recruited 64 NPC patients and collected samples after six month of radiotherapy. 32 patients were included into normal healing group (N), 22 patients were mild delayed healing group (M), while 10 patients were severe delayed healing group (S). 16S rRNA gene sequencing was used to assess and identify oral microbiota alteration. Results: The diversity of oral microbial communities was not significantly different. Composition of oral microbial was huge different among S group, for the Actinobacteria and Veillonella were significantly increased, which showed significant dysbiosis of the oral microbiome. Functional analysis of metabolic pathways of oral microbiota demonstrated that degradation of organic acids and amino acids were significantly increased in S group. Moreover, phenotype analysis found that relative abundance of aerobic and biofilm formation were higher in S group. We also found the Actinobacteria co-occurred with Veillonellaceae, but anti-occurred with other biofilm oral bacteria. These two biomarkers may be predictable for severe delayed healing of oral mucositis after radiotherapy. Conclusion: This study suggests a potential association between oral microbiome and delayed healing of oral mucositis. The Actinobacteria and Veillonellaceae may be biomarkers in predicting the risks for the severe delayed healing of oral mucositis after radiotherapy of NPC.